THE EFFECT OF USING PAIR CHECK LEARNING MODEL ON STUDENTS’ WRITING SKILL - Gusparia Gusparia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
The purpose of this study is to find out the effectiveness of pair check learning model on students’ writing skill of recount text. The research design was experimental by giving pre-test and post-test to the class. It involved 30 participants of SMPN 4 Pasir Penyu. The research question were posted in this study in order to find out the significant effect of using pair check learning model on students’ writing skill of recount text. Pretest and posttest were administered in this study and sample t-test was used to analyze the data. The research finding shows that there was significant effect of using pair check learning model on students’ writing skill of recount text. The data was analyzed by using t-test. It proved that this model can be used to teach recount text, the final test showed that from 30 students of experimental class, they got average 74.16 and S2 was 96.69 then controlled class got the average 38.66 and S2 was 92.44. Based on this data, it was done the t-test, and the result is tcount > table, it is 14.14 > 2.00. It means that this study is accepted. So, it can make inference that pair check learning model can be applied in teaching writing recount text especially at SMPN 4 Pasir Penyu.